(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with studying the spatial analysis of the uses of animal production in the province of Al-Qadisiyah by studying the classification of the uses of animal production in the province, then the geographical distribution of those uses, and analyzing the image of the spatial relationships of the uses of animal production with geographical variables in the study area, and addressing the problems facing these uses as well as the proposed solutions. For the problems facing the uses of animal production in the province.